If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(2+6x)=-231
We move all terms to the left:
7(2+6x)-(-231)=0
We add all the numbers together, and all the variables
7(6x+2)-(-231)=0
We add all the numbers together, and all the variables
7(6x+2)+231=0
We multiply parentheses
42x+14+231=0
We add all the numbers together, and all the variables
42x+245=0
We move all terms containing x to the left, all other terms to the right
42x=-245
x=-245/42
x=-5+5/6
| 0.05x+0.10(15-x)=0.90 | | 8z-3=4(z-3)+9+4+z | | -6(h+3)=-36 | | 15c=-30 | | (-p+71)+(3p-59)=2(-p+86) | | 9-b=3b-7 | | (2x-3)/4+x=(2x+3)/2+8 | | 8z-3=4(2-3)+9+4z | | 6-2/5=n | | x+2x+1/2(3x)=3 | | 5^2+10+20=y | | 3(w-4)-8=-6(-4w+5)-7w | | Y=-100x+800 | | 4x-0=17 | | 15x-7x=8 | | 10.3-x/18=5x-0.3/38 | | (-5)−5y=−15 | | 0=-16x^2+80x+6 | | 0-3y=17 | | 2x+14=6x+10 | | -4x+6+3x=10-3x+4 | | -5(y-2)=-2y+16 | | 3(12x+24)=x | | 5w=-7+6 | | 44-x-2x=50 | | 5/14*c=-1/2 | | 3x-x-6=36 | | x+4=19–2x | | -39=-8v+5(v-6) | | -4=7+z | | Z+1/9=2z+2/9 | | 6x+2=9x=14 |